School Efforts in Preventing Drug Abuse for Students in Vocational High Schools - Kurniawati, Kurniawati; Mediatati, Nani; Nugroho, Agus Bambang (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to know and describe the school’s efforts in preventing drug abuse (Narcotics, Psychotropic, and Other Addictive Substances) by students at SMK Negeri 2 Salatiga. There were five respondents, namely the Head of Student Affairs, counseling teacher, subject teacher (PPKn), one of the students, and the Drug Unit of Salatiga Police. This research uses qualitative methods, with data collection techniques through observation and interviews. The results showed that there are several efforts or activities that have been carried out by schools to prevent drug abuse by students, namely; 1) intracurricular activities carried out by subject teachers (PPKn, BK). 2) co-curricular activities, where this activity aims to deepen the material in intracurricular activities, such as the cooperation of counseling teachers with doctors who are more expert in the field of health. 3) extracurricular activities, which are activities outside of class hours, one of which is PMR. 4) school collaboration activities with other parties, namely BNN, Police / TNI. These activities are the efforts of SMK Negeri 2 Salatiga in preventing drug abuse.